Manfaat Buah Zaitun dalam Sains dan Al-Quran - Alam, Muhammad Tegar Bahrul; Fahruddin, M. Mukhlis (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2024)
Many plants and fruits are mentioned in the Qur'an. Allah has grown all kinds of plants and all forms of plants that exist on this earth. There are many scientific miracles regarding agricultural fields in the Qur'an, one of which is the Olive fruit. Olives have the scientific name Olea europaea which are spread in the Mediterranean countries, Africa, the Arabian peninsula, India, and Asia. Olives have many benefits such as reducing high blood pressure, facilitating urination, lowering blood sugar levels, containing anti-microbial substances and effective in dealing with viruses, bacteria, and fungi. The content of compounds contained in olives such as phenols, tocopherols, sterols, pigans and squalene have an important role in health and can cure several diseases. Olives also contain omega 9 and omega 3 which can function as anti-inflammatory. Keywords: fruit, olives, science, plants, integrity, the Koran